2006
DOI: 10.1007/s10592-006-9176-z
|View full text |Cite
|
Sign up to set email alerts
|

Levels of allozyme diversity in closely related toadflaxes (Linaria, Plantaginaceae) and their correspondence with the breeding systems of the species

Abstract: Toadflaxes (Linaria Miller) represent the largest genus of the tribe Antirrhineae (formerly included in the Scrophulariaceae) of the Plantaginaceae family. These taxa vary according to their ranges (narrow-regional-widespread), biological traits (duration, flower morphology, breeding system) and ecological preferences. No comparative genetic studies have been performed up to the moment and the levels and distribution of genetic diversity within this genus remain undocumented. We have conducted an allozyme stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…In our analyses, contrasting diversification rates are explained by unequal speciation rates, which are higher for xenogamous species (Table ). This result contrasts with recent research indicating that selfing may promote between‐population differentiation (Hamrick & Godt ; Charlesworth & Pannell ; see also Segarra‐Moragues & Mateu‐Andres for an example with some Linaria species) and speciation (Wendt et al . ; Martin & Willis ; Guo et al .…”
Section: Discussioncontrasting
confidence: 98%
“…In our analyses, contrasting diversification rates are explained by unequal speciation rates, which are higher for xenogamous species (Table ). This result contrasts with recent research indicating that selfing may promote between‐population differentiation (Hamrick & Godt ; Charlesworth & Pannell ; see also Segarra‐Moragues & Mateu‐Andres for an example with some Linaria species) and speciation (Wendt et al . ; Martin & Willis ; Guo et al .…”
Section: Discussioncontrasting
confidence: 98%
“…S8). For example, some of the shortest spurs in Linaria are found in species with tiny corollas that appear to have evolved as a result of self‐fertilization (Segarra‐Moragues & Mateu‐Andrés, ; Blanco‐Pastor & Vargas, ). After accounting for corolla size, evolution of the spur : corolla ratio also displays a pattern of recurrent changes with relatively homogeneous rates (Figs S9, S10), and model testing supports a nonphylogenetic model (Table ), indicating a high evolutionary lability.…”
Section: Discussionmentioning
confidence: 99%
“…The long life cycle and obligate outcrossing mating system (dioecy) of D. caputoi may be contributing factors which explain the high levels of allozyme diversity found in this study. It has been found that in systems where selfing is completely prevented, through dioecy (Costich & Meagher, 1992; Oostermeijer & De Knegt, 2004) or self‐incompatibility (Segarra‐Moragues & Mateu‐Andrés, 2007), allozyme diversity is higher within than among populations.…”
Section: Discussionmentioning
confidence: 99%